Genome-wide association study identifies a new locus JMJD1C at 10q21 that may influence serum androgen levels in men - Jin, Guangfu (Oxford University Press, 2012)
Circulating androgen levels are often used as indicators of physiological or pathological conditions. More than half of the variance for circulating androgen levels is thought to be genetically influenced. A genome-wide association study (GWAS) has identified two loci, SHBG at 17p13 and FAM9B at Xp22, for serum testosterone (T) levels; however, these explain only a small fraction of inter-individual variability. To identify additional genetic determinants of androgen levels, a GWAS of baseline serum T and dihydrotestosterone (DHT) levels was conducted in 3225 men of European ancestry from the REduction by DUtasteride of Prostate Cancer Events (REDUCE) study. Cross-validation was used to confirm the observed associations between the drug (n = 1581) and placebo (n = 1644) groups of REDUCE. In addition to confirming the associations of two known loci with serum T levels (rs727428 in SHBG: P = 1.26 × 10(−12); rs5934505 in FAM9B: P = 1.61 × 10(−8)), we identified a new locus, JMJD1C at 10q21 that was associated with serum T levels at a genome-wide significance level (rs10822184: P = 1.12 × 10(−8)). We also observed that the SHBG locus was associated with serum DHT levels (rs727428: P = 1.47 × 10(−11)). Moreover, two additional variants in SHBG [rs72829446, in strong linkage equilibrium with the missense variant D356N (rs6259), and rs1799941] were also independently associated with circulating androgen levels in a statistical scale. These three loci (JMJD1C, SHBG and FAM9B) were estimated to account for ∼5.3 and 4.1% of the variance of serum T and DHT levels. Our findings may provide new insights into the regulation of circulating androgens and potential targets for androgen-based therapy.